2013
DOI: 10.7196/samj.7111
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction in a cohort of South African children with Down syndrome

Abstract: Background. While international studies show thyroid dysfunction occurs more commonly in individuals with Down syndrome (DS) than in the general population, there is a paucity of available data from sub-Saharan Africa. Objectives. To document the range of thyroid function in a cohort of South African children with DS, and to assess referral and treatment practices when thyroid dysfunction was present. Methods. A retrospective file-based study of 391 children with DS seen at the genetic clinics at three Johanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
17
6
Order By: Relevance
“…Our observation of the association of hypothyroidism with the diarrheal children having Down syndrome is also understandable. In our study we found 9.3% babies had thyroid dysfunction among Down syndrome whereas the prevalence of thyroid disease with Down syndrome in previous studies involving nondiarrheal children was 4–18% [ 17 – 19 , 23 , 27 29 ]. Down syndrome was also found to be significantly associated with hypocalcemia.…”
Section: Discussioncontrasting
confidence: 66%
“…Our observation of the association of hypothyroidism with the diarrheal children having Down syndrome is also understandable. In our study we found 9.3% babies had thyroid dysfunction among Down syndrome whereas the prevalence of thyroid disease with Down syndrome in previous studies involving nondiarrheal children was 4–18% [ 17 – 19 , 23 , 27 29 ]. Down syndrome was also found to be significantly associated with hypocalcemia.…”
Section: Discussioncontrasting
confidence: 66%
“…Our observation of a high frequency of subclinical hypothyroidism in DS patients is similar to that of previous reports from India 1 and elsewhere. 2,3 We did not observe any cases of hyperthyroidism in this study. Subclinical hypothyroidism in infants and preschool children with DS is usually a transient condition, with remission in >70% of cases.…”
Section: Figure 1: A) Serum Tsh B) T3 C) T4 Levels In Down Syndromecontrasting
confidence: 50%
“…The most frequent among these are the thyroid abnormalities which range from subclinical to overt hypothyroidism, and rarely hyperthyroidism. [1][2][3] Individuals with DS are more susceptible to thyroid disorders compared to the general population. Primary hypothyroidism, referred to as elevated TSH, is the most common thyroid abnormality in DS; secondary hypothyroidism indicated by normal/reduced TSH is extremely rare.…”
Section: Thyroid Abnormalities Among Down Syndrome Children From Keramentioning
confidence: 99%
“…21 In our study, compensated/subclinical hypothyroidism has been found to be the most common (four of six cases of elevated TSH), as it shown in other studies. 6,7,22 Furthermore, transient hypothyroidism is the most common form of thyroid dysfunction observed in Down's syndrome patients. Mark Selikowitz in his longitudinal study observed that 40% of these cases of compensated hypothyroidism resolved spontaneously.…”
Section: Discussionmentioning
confidence: 99%